SEJARAH SOSIOLOGIS BUDAYA BERNAFKAH KOMUNITAS ADAT SUKU DUANO - Amrifo, Viktor; Dharmawan, Arya H.; Sunito, Satyawan; Soetarto, Endriatmo (History Department, Semarang State University and Historian Society of Indonesia, 2014)
The milestones of Duano Tribeâ€™s livelihood culture can be grouping into 4 periodes. The periodization based on the adaptation of Duano Tribe community toÂ bio-physic environment change or livelihood place change that used observation, interview, and document study to collect the data.Â The first is year before 1722 where they was a sea nomads in Malaka Strait. In this period, Duano Tribe developed their livelihood culture based on schooling fish hunting activity. The second is year since 1722 to 1932 where theÂ Duanoâ€™s livelihood place moved to caostal zone and small island of Malaka Strait. In this period,Â They developed livelihood culture based on sea nomads and fishingÂ technology, but natural culture that used in livelihood activity changed to pelagic fish and small fish. The third is year since 1932 to 1960, where the livelihood culture of Duano Tribe was in transition phase. In this period, livelihood activity of Duano Tribe changed to fishing activity at estuarin ecosystem in Berhala Strait. And the last is year after 1960, where the livelihood culture of Duano Tribe based on â€œmenongkahâ€ activity. Interaction between Duano community and state effect on their livelihood culture change. The adaptation of Duano Tribe community to bio-physic environment that was being effected by state power or another external power can be called as semi-natural adaptation.Keywords: Duano Tribe, Livelihood culture, Semi-natural adaptation, Sea nomads, FishermenTonggak-tonggak sejarah bernafkah Suku Duano yang dilihat dari adaptasi mereka terhadap lingkungan biofisik dapat dikelompokkan menjadi 4 periode. Pengelompokkan ini diperoleh melalui serangkaian proses pengumpulan data dengan teknik observasi, wawancara, dan studi literatur. Periode pertama adalah masa sebelum tahun 1722 dengan budaya bernafkah sebagai pengembara laut yang berburu ikan-ikan ruaya, periode kedua diantara tahun 1722 sampai 1932 sebagai pengembara laut yang berburu ikan-ikan perairan dangkal, periode ketiga dari tahun 1932 sampai 1960 sebagai peralihan dari pengembara laut ke nelayan menetap yang memanfaatkan sumberdaya perikanan muara-pantai, dan periode keempat setelah tahun 1960 sebagai nelayan menetap yang menangkap/menungumpulkan sumberdaya perikanan muara-pantai atau aktivitas menongkah. Interaksi Suku Duano dan negara mempengaruhi perubahan budaya bernafkah budaya bernafkah mereka. Perubahan budaya bernafkah yang dipengaruhi oleh kekuatan negara atau kekuatan lain diluar komunitas dapat disebut semi-natural adaptasi.Kata Kunci: Suku Duano, Budaya Bernafkah, Adaptasi Semi-natural, pengembara laut, nelayanÂ Â